Implementasi Pendaftaran Tanah Secara Elektronik di Kabupaten Malang - Budiastanti, Dhaniar Eka; Shanty, Wika Yudha; Rahayu, Dewi Ayu; Laila, Khotbatul; Gunawan Putri, Annisa Rizkita (University of Merdeka Malang, 2024)
The digitization era in Indonesia has brought about rapid technological advancement, leading to an increase in digital or electronic forms of human activities, particularly in land-related activities. To avoid land disputes, it is essential to ensure legal certainty regarding land rights status. This is achieved through electronic land registration carried out by the National Land Agency (BPN). Article 2 of the Regulation of the Minister of Agrarian Affairs/Head of BPN No. 1 of 2021 outlines the implementation of electronic land registration. This research aims to analyze the implementation of Article 2 of Regulation of the Minister of Agrarian Affairs/Head of BPN No. 1 of 2021 by the National Land Agency (BPN) of Malang Regency and identify the challenges faced by BPN Malang Regency in implementing the regulation. This research employs an empirical legal research method, which examines the effectiveness of law within society. The findings indicate that electronic land registration at the National Land Agency (BPN) of Malang Regency has been gradually progressing, with thirty thousand lands already registered. Challenges encountered include insufficient human resources, a significant portion of the population lacking technological literacy, and concerns regarding cybercrime and electronic certificate forgery.